2015
DOI: 10.1002/prp2.134
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of a selective and potent A2a agonist with extended lung retention

Abstract: Although the anti-inflammatory role of the A2a receptor is well established, controversy remains with regard to the therapeutic value for A2a agonists in treatment of inflammatory lung diseases, also as a result of unwanted A2a-mediated cardiovascular effects. In this paper, we describe the discovery and characterization of a new, potent and selective A2a agonist (compound 2) with prolonged lung retention and limited systemic exposure following local administration. To support the lead optimization chemistry p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, a range of other G protein-dependent and independent signaling mechanisms are associated with activation of ARs. 1 Nucleoside derivatives that activate ARs (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) are shown in Fig. 1, and AR antagonists (both nucleosides and nonnucleosides, 25-49) are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a range of other G protein-dependent and independent signaling mechanisms are associated with activation of ARs. 1 Nucleoside derivatives that activate ARs (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) are shown in Fig. 1, and AR antagonists (both nucleosides and nonnucleosides, 25-49) are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…17 Potent A 2A AR agonist UK432,097 12 failed clinical trials for COPD, but displays extended lung retention. 18 Lexiscan 13a is a short acting A 2A AR agonist that is approved for dilating coronary vessels during stress testing and was recently demonstrated to open the blood-brain barrier transiently, with a decreased Pglycoprotein expression, and to ameliorate sickle cell disease. [19][20][21] Its A 2A AR affinity and selectivity are only moderate (K i *1.3 mM, >10-fold selective versus A 1 AR).…”
Section: Introductionmentioning
confidence: 99%
“…UK-432,094 was tested by PFIZER in a phase II clinical trial (ClinicalTrials.gov Identifier: NCT00430300) as an inhalation agent for severe chronic obstructive pulmonary disease; however, the trial was terminated due to low treatment effectiveness. UK-432094 is a selective A 2A agonist (Ki of 4.75 nM) [108], with reported EC 50 as low as 5.4 ±1.8 nM (cAMP level evaluation in CHO cells stably expressing human A 2A and A 2B receptors) [109]. Its anti-platelet effect has been recently assessed using multiple electric aggregometry in whole blood.…”
Section: Adenosine Receptor Agonists—structure Chemical Propertiementioning
confidence: 99%
“…Recent investigative toxicology study of a potent and selective A 2A AdR agonist for potential treatment of inflammatory lung diseases showed cardiotoxic response. Single‐dose rat study (150 μg/kg) revealed myocardial necrosis with several foci together with perivascular and ventricular oedema, whereas during repeated dose study (30 μg/kg per 4 days) fibrotic heart tissue has developed . Mechanisms of cardiovascular toxicity still remain uncertain but appear to be partly related to excessive induction of endothelial nitric oxide synthase .…”
Section: Organ‐specific Toxicity Of Adenosine Derivatives and Adenosimentioning
confidence: 99%
“…Single-dose rat study (150 lg/kg) revealed myocardial necrosis with several foci together with perivascular and ventricular oedema, whereas during repeated dose study (30 lg/kg per 4 days) fibrotic heart tissue has developed. [119] Mechanisms of cardiovascular toxicity still remain uncertain but appear to be partly related to excessive induction of endothelial nitric oxide synthase. [120] It was also suggested from multiple sources that some antidepressants (citalopram, amitriptyline) may cause QRS/QT prolongation activating A 1 AdRs.…”
Section: Cardiovascular Toxicitymentioning
confidence: 99%